2010
DOI: 10.1542/peds.2009-2427
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Informed Consent Process for a Pediatric Resuscitation Trial

Abstract: Parents endorsed resuscitation research with an exception from informed consent. Public disclosure yielded >80% parental awareness. Efforts should be made to ensure awareness of the ability to opt out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 11 publications
0
22
0
1
Order By: Relevance
“…Problems with comprehension and readability [11], a misconception of direct therapeutic benefit [9, 12], and not recognizing the ability to discontinue [9] or opt out of treatment [13] also impede the function of the informed consent process. Importantly, the decision making process involving informed consent may be flawed, especially in high pressure environments [14].…”
Section: Introductionmentioning
confidence: 99%
“…Problems with comprehension and readability [11], a misconception of direct therapeutic benefit [9, 12], and not recognizing the ability to discontinue [9] or opt out of treatment [13] also impede the function of the informed consent process. Importantly, the decision making process involving informed consent may be flawed, especially in high pressure environments [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although parental involvement in PIC trials is similarly limited, with few examples identified, 52,53 parents' experiences and views of NIC trials have been relatively well studied: we have identified 21 papers. 49,51,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] Many of these papers focus on issues at the 'front end' of trials, such as comprehension, decision-making and views of enrolment in more than one trial.…”
Section: Experiences In Neonatal Intensive Care Units and Paediatric mentioning
confidence: 99%
“…Understanding and recalling information is difficult for parents in the research context [54] and they also overestimate their understanding [55]. Written information and posters are identified by parents in the PICU as useful information tools in the informed consent process [48,56].…”
Section: Understandingmentioning
confidence: 99%
“…They favor dialogue with the community, which is informed about the project beforehand and its results afterwards [58]. Raymond et al [56] describe an efficient method of in-hospital community consultation for a trial of vasopressin added to adrenaline in cardiac arrest in the PICU. All parents were informed about the trial through posters, written information, a website, and the research team, and were offered the possibility to opt out of the study.…”
Section: Waiver Of Consentmentioning
confidence: 99%